Nutritional quality of protein flours of fava bean (Vicia faba L.) and in vitro digestibility and bioaccesibility - Ayala Rodríguez, Victor Andrés; López Hernández, Abad Arturo; López Cabanillas Lomelí, Manuel; González Martínez, Blanca Edelia; Vázquez Rodríguez, Jesús Alberto (2022)
Fava bean (Vicia faba L.) is a high-protein crop consumed worldwide and is an exceptional plant-based protein source for human consumption. The present study evaluated in vitro nutritional properties of four different protein flours of fava bean: minimal processed flour (MPF), cooked flour (CF), non-polyphenol protein concentrate (NPP), and polyphenol-protein concentrate (PP). NPP showed the highest protein concentration of 94.39 ± 0.76%. The heat treatment significantly increased the in vitro protein digestibility in CF (94.15 ± 2.45%). NPP and PP showed the highest bioaccessibility, 29.85 ± 1.88 and 33.19 ± 1.65%, respectively, no significant differences. SDS-PAGE analysis revealed bioaccessible low molecular weight peptides (<15 kDa) and legumin and vicilin presence. In silico analysis of bioactive peptides of legumin and vicilin presented high occurrence frequencies of bioactivities, as angiotensin-converting enzyme-inhibitor and dipeptidyl peptidase III/IV inhibitor peptides. This study supports the use and further investigation of fava bean proteins for human nutrition.